Anti-cytokine therapy for rheumatoid arthritis. - Maini, R; Taylor, P (2000)
Tumor necrosis factor alpha (TNF alpha) and interleukin-1 (IL-1) are important in mediating inflammation in rheumatoid arthritis (RA). Randomized phase II and III clinical trials of anti-TNF reagents (infliximab and etanercept) have demonstrated an acceptable safety profile and marked clinical efficacy in cases of RA that have not responded adequately to conventional therapy. Combination therapy with methotrexate (MTX) appears to be particularly effective in patients whose disease activity persists despite prior disease-modifying antirheumatic drugs (DMARDs) and ongoing MTX monotherapy. DMARD-recalcitrant disease may become the main indication for the use of anti-TNF drugs in patients with RA. Trials of IL-1 receptor antagonist show a relatively modest anti-inflammatory effect and a possible retardation of joint damage. Whether anti-TNF therapy protects joints from structural damage is under investigation. One anti-TNF reagent has already been approved in the United States for the treatment of RA, and other cytokine antagonists or agonists are under development.